Metal Sulfides as Sensing Materials for Chemoresistive Gas Sensors - Gaiardo, Andrea (Sensors (Basel), 2016)
This work aims at a broad overview of the results obtained with metal-sulfide materials in the field of chemoresistive gas sensing. Indeed, despite the well-known electrical, optical, structural and morphological features previously described in the literature, metal sulfides present lack of investigation for gas sensing applications, a field in which the metal oxides still maintain a leading role owing to their high sensitivity, low cost, small dimensions and simple integration, in spite of the wide assortment of sensing materials. However, despite their great advantages, metal oxides have shown significant drawbacks, which have led to the search for new materials for gas sensing devices. In this work, Cadmium Sulfide and Tin (IV) Sulfide were investigated as functional materials for thick-film chemoresistive gas-sensors fabrication and they were tested both in thermo- and in photo-activation modes. Furthermore, electrical characterization was carried out in order to verify their gas sensing properties and material stability, by comparing the results obtained with metal sulfides to those obtained by using their metal-oxides counterparts. The results highlighted the possibility to use metal sulfides as a novel class of sensing materials, owing to their selectivity to specific compounds, stability, and the possibility to operate at room temperature.